Wearable Systems of Reconfigurable Microneedle Electrode Array for Subcutaneous Multiplexed Recording of Myoelectric and Electrochemical Signals - Zhengjie Liu; Chuanjie Yao; Xingyuan Xu; Xinshuo Huang; Shuang Huang; Shantao Zheng; Tao Zhang; Yan Li; Fanmao Liu; Yuxiang Wu; Jing Liu; Hui‐jiuan Chen; et al. (Advanced Science, 2025)
Abstract The real‐time monitoring of in vivo electrophysiological and biochemical signals provides critical insights into the activities of tissues and organs. As the activity and metabolic state of different sites in the muscle vary, multichannel detection is necessary to capture the functional state of the whole muscle, yet the access to the bio‐information in subcutaneous space remained challenging. This work reports the development of a reconfigurable microneedle electrode array integrated system designed to achieve painless and minimally invasive monitoring of subcutaneous electromyogram (EMG), oxygen species, and pH through an array of thumbtack‐shaped microneedle (TSMN) electrode. By assembling discrete TSMNs into an array, the system enables multi‐parameter detection with single microneedle resolution. The PEDOT: PSS layer is electrochemically deposited on the TSMNs, enhancing their signal‐sensing capabilities and electrochemical properties. Additionally, the design of the pogo pin interface ensures reliable signal transmission and stable device performance, while allowing flexible replacement of the TSMNs, which enhances system maintainability and longevity. Validation experiments conducted on in vivo animal models demonstrate the system's capability in real‐time monitoring of muscle fatigue and indicators related to sciatic nerve injury. These results advance the development of wearable technologies for monitoring subcutaneous physiological and biochemical information for diagnosing neuromuscular disorders.